Career progression and formal versus on-the-job training - Jérôme Adda; Christian Dustmann; Costas Meghir; Jean-Marc Robin (Institute for Fiscal Studies (IFS), 2006)
We develop a dynamic discrete choice model of training choice, employment and wage growth, allowing for job mobility, in a world where wages depend on firm-worker matches, as well as experience and tenure and jobs take time to locate. We estimate this model on a large administrative panel data set which traces labour market transitions, mobility across firms and wages from the end of statutory schooling. We use the model to evaluate the life-cycle return to apprenticeship training and find that on average the costs outweigh the benefits; however for those who choose to train the returns are positive. We then use our model to consider the long-term lifecycle effects of two reforms: One is the introduction of an Earned Income Tax Credit in Germany, and the other is a reform to Unemployment Insurance. In both reforms we find very significant impacts of the policy on training choices and on the value of realised matches, demonstrating the importance of considering such longer term implications.
Keywords: 330; Rentenfinanzierung; Umlageverfahren; Kapitaldeckungsverfahren; Finanzpolitik; Overlapping Generations; Risiko; Theorie